Sexual health and well-being during antenatal care: addressing global gaps in healthcare provision - Gulma, Kabiru Abubakar; Musa, Abubakar Isa (International Journal of Public Health Science (IJPHS), 2025)
This paper highlights the importance of addressing sexual health and well-being in antenatal care, which goes beyond the absence of reproductive disease to include physical, mental, and social aspects. Central to sexual health is the quality of the relationship between expectant parents, which can influence the future well-being of both the parents and their child. Despite this, current antenatal care often fails to address sexual health due to healthcare providers' lack of training and fears of offending patients when discussing intimate issues. The paper suggests that antenatal care might be viewed as an inadequate environment to handle such sensitive matters—due to time constraints and perceived intrusiveness, it could be an optimal time for discussions, as parents-to-be are particularly attuned to relationship health during pregnancy. The paper also focuses on adolescent mothers as a globally neglected group in terms of sexual health support during pregnancy, despite the significant role they play in ensuring intergenerational well-being. The broader healthcare system, however, continues to treat sexual health and well-being as taboo subjects, leaving a gap in global antenatal services. As research underscores the importance of a strong parental relationship for the socio-emotional development of the child, the paper advocates for integrating sexual health into antenatal care to enhance both parental well-being and child development. However, this area remains underexplored in many parts of the world due to cultural sensitivities and limited healthcare infrastructure.